Methane Emission from Digestion of Palm Oil Mill Effluent (POME) in a Thermophilic Anaerobic Reactor - I Irvan; Bambang Trisakti; Vivian Wongistani; Yoshimasa Tomiuchi (International Journal of Science and Engineering, 2012)
As the issue of global warming draws increasing concern, many studies to reduce CO2 and CH4 gases (greenhouse gases, GHG) have been implemented in several countries, including in Indonesia. Considering that Indonesia has a huge numbers of palm oil mills, no doubt if their waste water treatment as one of the major sources in GHG.  This paper presents the results from a research project between Metawater Co., Ltd.-Japan and University of Sumatera Utara-Indonesia. The objective of the research is to study the methane emission of thermophilic fermentation in the treatment of palm oil mill effluent (POME) on a laboratory scale. Anaerobic digestion was performed in two-litre water jacketed biodigester type continuous stirred tank reactor (CSTR) and operated at a thermophilic temperature (55 oC). As raw material, a real liquid waste (POME) from palm oil mill was used. Fresh POME was obtained from seeding pond of PTPN II waste water treatment facility which has concentration of 39.7 g of VS/L and COD value of 59,000 mg/L. To gain precise results, complete recording and reliable equipment of reactor was employed. As the experimental results, for hydraulic retention time (HRT) 8 days, VS decomposition rate of 63.5% and gas generation of 6.05-9.82 L/day were obtained, while for HRT 6 and 4 days, VS decomposition rate of 61.2, 53.3% and gas generation of  6.93-8.94  and  13.95-16.14 L/day were obtained respectively. Keywords—methane (CH4), palm oil mill effluent (POME), anaerobic digestion, thermophilic, green house gases (GHG)